2018
DOI: 10.1177/0967391118816393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low nanoclay content on the physico-mechanical properties of poly(lactic acid) nanocomposites

Abstract: In this work, three different nanoclays (1.44P, 1.34MN, and Cloisite 15A) were used to reinforce an injection grade poly(lactic acid) (PLA). The nanocomposites (NCs) were prepared using three different nanoclay concentration levels (1, 3, and 5 wt%) in a twin-screw extruder. To evaluate their mechanical performance (static and dynamic tests) and thermal properties, the respective samples were obtained by injection molding. Results showed that the three nanoclays significantly increased the tensile and flexural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…6. The inclusion of nanoclay in the PLA did not show any significant effect in the impact strength, as it was reported before by Robledo-Ortíz et al (2019) probably due to the low amount of nanoclay content which is not significant in comparison to the high values of absorbed energy supported by the neat PLA. Jandas et al (2013) reported that impact strength decreased with the addition of modified montmorillonite to PLA.…”
Section: Impact Strength Propertiessupporting
confidence: 53%
“…6. The inclusion of nanoclay in the PLA did not show any significant effect in the impact strength, as it was reported before by Robledo-Ortíz et al (2019) probably due to the low amount of nanoclay content which is not significant in comparison to the high values of absorbed energy supported by the neat PLA. Jandas et al (2013) reported that impact strength decreased with the addition of modified montmorillonite to PLA.…”
Section: Impact Strength Propertiessupporting
confidence: 53%
“…Their ductility is also not reduced as they all break at around ~30% of strain. This gain can be attributed to reduced creep by the presence of HNT nanoclay or increased crystallinity owing to the nucleating effect of HNTs [ 28 , 29 , 30 ]. However, further addition of HNTs diminished the gain and for 10 vol.% content of HNTs, the tensile strength is even reduced by 7%, while the strain to break is reduced to 2.8%.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another reason for decrease in impact strength may be the stiffening of polymer chains which result in less ability to absorb impact energy. 34,35…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another reason for decrease in impact strength may be the stiffening of polymer chains which result in less ability to absorb impact energy. 34,35 Figure 9 shows the hardness of composites containing different contents of NS, NC, and NSNC. Incorporation of NS at (2, 4, and 6 phc) slightly increased the hardness by 1.45%, 3%, and 5.1%, respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 99%